Birds of Stone : Chinese Avian Fossils from the Age of Dinosaurs - Chiappe, Luis M. (Book collections on Project MUSE., 2016)
When fossils of birds from China's Jehol region first appeared in scientific circles, the world took notice. These Mesozoic masterpieces are between 120 and 131 million years old and reveal incredible details that capture the diversity of ancient bird life. Paleontologists all over the world began to collaborate with Chinese colleagues as new and wondrous fossil-related discoveries became regular events. The pages of National Geographic and major scientific journals described the intricate views of feathers as well as food still visible in the guts of these ancient birds. Now, for the first time, a sweeping collection of the most interesting of Jehol's avian fossils is on display in this beautiful book. Birds of Stone makes visible the unexpected avian diversity that blanketed the earth just a short time (geologically speaking) after a dinosaur lineage gave rise to the first birds. Our visual journey through these fossils is guided by Luis M. Chiappe, a world expert on early birds, and Meng Qingjin, a leading figure in China's natural history museum community. Together, they help us understand the "meaning" of each fossil by providing straightforward narratives that accompany the full-page photographs of the Jehol discoveries. Anyone interested in the history of life-from paleontologists to inquisitive birders-will find Birds of Stone an irresistible feast for the eyes and mind.